Should HIV testing for all pregnant women continue? Cost‐effectiveness of universal antenatal testing compared to focused approaches across high to very low HIV prevalence settings. Issue 1 (14th December 2016) - Ishikawa, Naoko; Dalal, Shona; Johnson, Cheryl; Hogan, Daniel R; Shimbo, Takuro; Shaffer, Nathan; Pendse, Razia N; Lo, Ying‐Ru; Ghidinelli, Massimo N; Baggaley, Rachel
Abstract : Introduction: HIV testing is the entry point for the elimination of mother‐to‐child transmission of HIV. Decreasing external funding for the HIV response in some low‐ and middle‐income countries has triggered the question of whether a focused approach to HIV testing targeting pregnant women in high‐burden areas should be considered. This study aimed at determining and comparing the cost‐effectiveness of universal and focused HIV testing approaches for pregnant women across high to very low HIV prevalence settings. Methods: We conducted a modelling analysis on health and cost outcomes of HIV testing for pregnant women using four country‐based case scenarios (Namibia, Kenya, Haiti and Viet Nam) to illustrate high, intermediate, low and very low HIV prevalence settings. We used subnational prevalence data to divide each country into high‐, medium‐ and low‐burden areas, and modelled different antenatal and testing coverage in each. Results: When HIV testing services were only focused in high‐burden areas within a country, mother‐to‐child transmission rates remained high ranging from 18 to 23%, resulting in a 25 to 69% increase in new paediatric HIV infections and increased future treatment costs for children. Universal HIV testing was found to be dominant (i.e. more QALYs gained with less cost) compared to focused approaches in the Namibia, Kenya and Haiti scenarios. The universal approach was also very cost‐effective compared to focused approaches, with $ 125 per quality‐adjusted life years gained in the Viet Nam‐based scenario of very low HIV prevalence. Sensitivity analysis further supported the findings. Conclusions: Universal approach to antenatal HIV testing achieves the best health outcomes and is cost‐saving or cost‐effective in the long term across the range of HIV prevalence settings. It is further a prerequisite for quality maternal and child healthcare and for the elimination of mother‐to‐child transmission of HIV.